Tuli Mengaji Goes Digital Instagram as a Cooperative Communication and Social Marketing Strategies for Inclusive Islamic Philanthropy - Ulva Lathifah; Rocky Prasetyo Jati (DAWUH : Islamic Communication Journal, 2026)
The digital transformation of Islamic philanthropy has created new opportunities for inclusive social engagement, yet the strategic use of social media platforms as channels integrating cooperative communication and social marketing remains underexplored, particularly regarding disability-inclusive programs. This study examines how LAZNAS PPPA Daarul Qur'an leverages Instagram as a cooperative communication and social marketing channel to communicate the "Tuli Mengaji" program, an inclusive Quranic education initiative designed for the Deaf community. Grounded in a Cooperative Communication framework (Jati, 2023), Integrated Marketing Communication (IMC), and the AIDA persuasion model, this qualitative case study analyzes message construction, content strategies, and audience responses generated through the official Instagram account @daarul_quran. Data were collected through non-participant observation of Instagram content, in-depth interviews with digital communication managers, and campaign documentation. Thematic analysis following Miles and Huberman's interactive model was employed to identify dominant communication patterns. Findings reveal that the organization employs emotionally resonant visual storytelling, participatory content co-creation, consistent faith-based messaging, and strategic calls-to-action aligned with both IMC and cooperative communication principles across Instagram's multiple content formats. The AIDA model is evident in how content progression moves audiences from initial attention toward donation behavior. The study contributes an initial conceptual model of inclusive digital social marketing for Islamic philanthropy institutions, embedding cooperative communication as a key mechanism of audience engagement and empowerment, offering theoretical and practical implications for nonprofit communication in the digital era.